Analysis of the Legal Outputs of State Institutions: The Case of the Constitutional Court of the Republic of Indonesia - Ahmad, Andi (Enigma Institute, 2023)
The Constitutional Court (MK) safeguards the constitution, specifically the 1945 Constitution of the Republic of Indonesia. The Constitutional Court issues a variety of legal documents, including decisions, decrees, rules, and rulings, as part of its responsibilities and jurisdiction. The ruling of the Constitutional Court carries paramount significance as a legal outcome. The ruling of the Constitutional Court is conclusive and obligatory, applying to both governmental bodies, individuals, and legal companies. The rulings made by the Constitutional Court have the power to nullify or modify laws, government regulations, presidential regulations, ministerial regulations, or regional rules that are in contradiction with the 1945 Constitution of the Republic of Indonesia. The decrees of the Constitutional Court can establish rules for the process of reviewing cases, the selection and appointment of constitutional judges, and other subjects concerning the responsibilities and powers of the Constitutional Court. Constitutional Court rules are legally enforceable items that typically serve as regulatory measures. The regulations of the Constitutional Court might govern issues pertaining to the administration and management of the Constitutional Court, as well as other concerns concerning the responsibilities and jurisdiction of the Constitutional Court. The decisions made by the MK can govern various aspects pertaining to cases under its jurisdiction, including the determination of court expenses, the appointment of temporary judges, and other relevant topics concerning the case. The legal outputs of the Constitutional Court play a crucial role in upholding the constitution, ensuring law enforcement, and safeguarding human rights in Indonesia.